"It's a proactive intervention instead of a reactive one": measuring facilitators and barriers regarding readiness to implement a treatment program for infants with neonatal opioid withdrawal syndrome - Leah Holcomb; Caitlin Koob; Rachel Mayo; Elizabeth Charron; Lori Dickes; Windsor Sherrill; Jennifer Hudson (BMC, 2023)
Abstract Background Managing Abstinence in Newborns (MAiN) is an evidence-based, cost-saving approach to caring for infants at risk of developing neonatal opioid withdrawal syndrome (NOWS). MAiN provides medication management in combination with education and is being implemented in hospitals across South Carolina (SC). This expansion of MAiN throughout the state includes educational training for providers on managing NOWS symptomology and evaluation support for data collection and analysis. This evaluation assessed the readiness of hospitals to implement MAiN by identifying potential barriers and facilitators to early program adoption. Methods We used the Consolidated Framework for Implementation Framework (CFIR) to guide the evaluation. As part of the ongoing evaluation of MAiN implementation, brief, structured interviews were conducted with healthcare providers (n = 82) at seven hospitals between 2019 and 2022 to learn more about perceived barriers and facilitators to implementation readiness. Two coders independently reviewed all transcripts and used deductive thematic analysis to code qualitative data using Atlas.ti Web using the established CFIR codebook. Results We identified barriers and facilitators to implementing MAiN in all five CFIR domains. Providers identified MAiN as an evidence-based, patient-centered model with the flexibility to adapt to patients' complex needs. Specific champions, external support, alignment with providers' personal motivation, and an adaptable implementation climate were identified as facilitators for implementation readiness. Barriers included a lack of consistent communication among hospital providers, minimal community resources to support patients and families after discharge, and a lack of provider buy-in early in implementation. Conclusions Key barriers and facilitators of MAiN implementation readiness were identified at seven participating hospitals throughout SC. Communication, staff and hospital culture and climate, and internal and external resource were all reported as essential to implementation. These findings could inform the MAiN program expansion in hospitals across SC.